N-Heterocyclic carbene-catalyzed diastereoselective synthesis of β-lactone-fused cyclopentanes using homoenolate annulation reaction - Mukherjee, Subrata; Mondal, Santigopal; Patra, Atanu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
NHC-catalyzed annulation of enals with 2-enoylpyridines or 2-enoylpyridine N-oxides leading to the diastereoselective synthesis of β-lactone-fused cyclopentanes is reported. The reaction proceeds via the generation of homoenolate equivalent intermediates and tolerates a broad range of functional groups.

Enantioselective synthesis of spirocyclohexadienones by NHC-catalyzed formal [3+3] annulation reaction of enals - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
The enantioselective synthesis of pyrazolone-fused spirocyclohexadienones was demonstrated by the reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones under oxidative N-heterocyclic carbene (NHC) catalysis. This atom-economic and formal [3+3] annulation reaction proceeds through a vinylogous Michael addition/spiroannulation/dehydrogenation cascade to afford spirocyclic compounds with an all-carbon quaternary stereocenter in moderate to good yields and excellent ee values. Key to the success of the reaction is the cooperative NHC-catalyzed generation of chiral alpha,beta-unsaturated acyl azoliums from enals, and base-mediated tandem generation of dienolate/enolate intermediates from pyrazolinones.
Keywords: annulation reactions; asymmetric catalysis; N-heterocyclic carbenes; organocatalysis; spiro compounds

Enantioselective synthesis of functionalized β-lactones by NHC-catalyzed aldol lactonization of ketoacids - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
N-Heterocyclic carbene (NHC)-catalyzed intramolecular aldol lactonization of readily available ketoacids leading to the enantioselective synthesis of cyclopentane-fused β-lactones is presented. The reaction proceeds via the generation of NHC-bound enolate intermediates formed from the ketoacids in the presence of the peptide coupling reagent HATU and NHC generated from the chiral triazolium salt. The functionalized β-lactones are formed under mild conditions in high yields and enantioselectivities.

Enantioselective synthesis of spiro γ-butyrolactones by N-heterocyclic carbene (NHC)-catalyzed formal [3+2] annulation of enals with 3-hydroxy oxindoles - Mukherjee, Subrata; Joseph, Sumi; Bhunia, Anup; Gonnade, Rajesh Ghanshyam; Reddy, Santhi Vardhan; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2017)
The N-heterocyclic carbene (NHC)-catalyzed enantioselective formal [3 + 2] annulation of α,β-unsaturated aldehydes with 3-hydroxy oxindoles is presented. Under oxidative conditions using the bisquinone oxidant, the reaction resulted in the synthesis of spiro γ-butyrolactones in moderate to good yields, enantioselectivity and diastereoselectivity. The reaction likely proceeds via the generation of the NHC-bound α,β-unsaturated acylazolium intermediate from enals, which was intercepted by the dioxindoles in a formal [3 + 2] pathway to form the spirocyclic compounds. However, a deeper mechanistic investigation revealed that the reaction can also proceed via the homoenolate intermediate. In this case, the dioxindole was oxidized to the corresponding isatin derivative using traces of air under basic conditions, and was intercepted with the NHC-bound homoenolate intermediate in a formal [3 + 2] pathway to afford the spiro compound.

N - heterocyclic - carbene - catalyzed umpolung of imines - Patra, Atanu; Mukherjee, Subrata; Das, Tamal Kanti; Jain, Shailja; Gonnade, Rajesh Ghanshyam; Biju, Akkattu T. (Angewandte Chemie International Edition, 2017)
N-Heterocyclic carbene (NHC) catalysis has been widely used for the umpolung of aldehydes, and recently for the umpolung of Michael acceptors. Described herein is the umpolung of aldimines catalyzed by NHCs, and the reaction likely proceeds via aza-Breslow intermediates. The NHC-catalyzed intramolecular cyclization of aldimines bearing a Michael acceptor resulted in the formation of biologically important 2-(hetero)aryl indole 3-acetic-acid derivatives in moderate to good yields. The carbene generated from the bicyclic triazolium salt was found to be efficient for this transformation.

N-Heterocyclic carbene-catalyzed aldol-lactonization of ketoacids via dynamic kinetic resolution - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh; Biju, Akkattu T. (ACS Catalysis, 2017)
N-Heteroryclic carbene (NHC)-catalyzed enantioselective aldol lactonization of acyclic ketoacids, proceeding via dynamic kinetic resolution, is presented. The carbene generated from the chiral anninoinclanol-derived triazolium salt in the presence of LiCl was the key for the success of this transformation. The reaction allowed the diastereoselective and enantioselective synthesis of cyclopentane-fused beta-lactones having three contiguous stereocenters. The reaction products are shown to undergo substrate-controlled beta-lactone opening in the presence of amines to afford succinimide derivatives with four contiguous stereocenters.
Keywords: aldol lactonization; beta-lactones; DKR strategies; ketoacids; N-heterocyclic carbenes; organocatalysis

Organocatalytic enantioselective vinylogous michael-aidoi cascade for the synthesis of spirocyclic compounds - Mondal, Santigopal; Mukherjee, Subrata; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2017)
Enantioselective synthesis of pyrazolone-fused spirocyclohexenols by the secondary amine-catalyzed cascade reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones is reported. This formal [3 + 3] organocascade reaction proceeds through a vinylogous Michael-aldol sequence to furnish the spiroheterocycles with three stereocenters including an all-carbon quaternary center in good yields and selectivities. The catalytic generation of alpha,beta-unsaturated iminium ions from enals and tandem dienolate/enolate formation from pyrazolinones are the key for the success of this spiroannulation reaction.

Enantioselective N-heterocyclic carbene-catalyzed cascade reaction for the synthesis of pyrroloquinolines via N-H functionalization of indoles - Mukherjee, Subrata; Shee, Sayan; Poisson, Thomas; Besset, Tatiana; Biju, Akkattu T. (Organic letters, 2018)
Functionalization of the indole N-H bond for enantioselective synthesis of biologically important pyrroloquinoline derivatives has been reported under oxidative N-heterocyclic carbene catalysis conditions. The interception of catalytically generated chiral alpha,beta-unsaturated acylazoliums with the indole derivatives proceeds in an aza-Michael/Michael/lactonization sequence to deliver the pyrroloquinoline derivatives in good yields, diastereoselectivities, and enantioselectivities. The simultaneous enhancement of reactivity and selectivity observed in polar aprotic solvents is noteworthy.

N-Heterocyclic carbene-catalyzed enantioselective synthesis of spiro-glutarimides via alpha,beta-unsaturated acylazoliums - Mondal, Santigopal; Ghosh, Arghya; Mukherjee, Subrata; Biju, Akkattu T. (Organic Letters, 2018)
NHC-catalyzed enantioselective [3 + 3] spiro-annulation of alpha,beta-unsaturated aldehydes with cyclic beta-ketoamides allowing the preparation of synthetically and biologically important spiro-glutarimide derivatives has been reported. The interception of the ketoamides with catalytically generated chiral alpha,beta-unsaturated acylazoliums proceeds in a Michael addition-intramolecular amidation pathway to deliver the spirocyclic products with good yield, diastereoselectivity, and enantioselectivity.

N-Heterocyclic carbene-catalyzed michael-michael-lactonization cascade for the enantioselective synthesis of tricyclic delta-lactones - Mukherjee, Subrata; Ghosh, Arghya; Marelli, Udaya Kiran; Biju, Akkattu T. (Organic Letters, 2018)
Enantioselective synthesis of tricyclic delta-lactones with three contiguous stereocenters has been demonstrated by the N-heterocyclic carbene (NHC)-catalyzed functionalization of benzylic C(sp(3))-H bonds. The NHC-catalyzed reaction of enals with dinitrotoluene derivatives under oxidative conditions proceeds via the chiral alpha,beta-unsaturated acylazoliums and produces the delta-lactones in good yields and excellent diastereoselectivity and enantioselectivity. This mild and atom-economic cascade reaction takes place in a Michael/Michael/lactonization sequence and tolerates a broad range of functional groups.

Recent advances in the organocatalytic enantioselective synthesis of functionalized -lactones - Mukherjee, Subrata; Biju, Akkattu T. (Chemistry-An Asian Journal, 2018)
This Focus Review highlights recent developments in the organocatalytic enantioselective synthesis of -lactone derivatives. Owing to the importance of -lactones as a heterocyclic motif that is present in a variety of natural products and biologically active molecules, several catalytic methods have been developed for the synthesis of these compounds in their enantiomerically pure form. Organocatalytic methods that employ N-heterocyclic carbenes (NHCs), cinchona alkaloids, isothioureas, 4-dimethylaminopyridine (DMAP) derivatives, and phosphines have allowed the highly enantioselective synthesis of -lactones from cheap and readily available starting materials. Moreover, the inherent strain in the four-membered ring of -lactones has also been utilized in further synthetic transformations, thus making -lactones a versatile intermediate in organic synthesis.

Synthesis of 2-Aryl naphthoquinones by the cross-dehydrogenative coupling involving an NHC-catalyzed endo-stetter reaction - Ghosh, Arghya; Patra, Atanu; Mukherjee, Subrata; Biju, Akkattu T. (Journal of Organic Chemistry, 2019)
An N-heterocyclic carbene (NHC)-catalyzed intramolecular Stetter reaction proceeding via the endo-fashion was the key step for the transition-metal-free and mild cross-dehydrogenative coupling of 2-cinnamoyl benzal-dehydes allowing for the synthesis of 2-aryl naphthoquinones. In this transformation, the carbene generated from the triazolium salt using Na2CO3 catalyzes the intramolecular Stetter reaction, which was followed by air oxidation to reinstall the C-C double bond.

Enantioselective synthesis of tricyclic beta-lactones by NHC-catalyzed desymmetrization of cyclic 1,3-diketones - Shee, Sayan; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2020)
The NHC-catalyzed desymmetrization of cyclic-1,3-diketones allowing the enantioselective construction of tricyclic beta-lactones with five contiguous stereocenters, including two quaternary stereocenters, has been developed. The mild and operationally simple addition of a-bromoenals to cyclopentane-1,3-diketone derivatives proceeds via the initial formation of chiral alpha,beta-unsaturated acylazolium intermediates and culminates in a cascade reaction, following the Michael-aldol-Iactonization pathway to deliver the beta-lactone derivatives in moderate to good yields and excellent selectivity.

NHC-catalyzed desymmetrization of N-aryl maleimides leading to the atroposelective synthesis of N-Aryl succinimides - Barik, Soumen; Shee, Sayan; Das, Soumik; Gonnade, Rajesh G.; Jindal, Garima; Mukherjee, Subrata; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2021)
Although the construction of axially chiral C-C bonds leading to the atroposelective synthesis of biaryls and allied compounds are well-known, the related synthesis of compounds bearing axially chiral C-N bonds are relatively rare. Described herein is the N-heterocyclic carbene-catalyzed atroposelective synthesis of N-aryl succinimides having an axially chiral C-N bond via the desymmetrization of N-aryl maleimides. The NHC involved intermolecular Stetter-aldol cascade of dialdehydes with prochiral N-aryl maleimides followed by oxidation afforded N-aryl succinimides in good yields and ee values. Preliminary studies on rotation barrier for the C-N bond, the temperature dependence, and detailed DFT studies on mechanism are also provided.
Keywords: asymmetric catalysis; axial chirality; desymmetrization; N-heterocyclic carbenes; organocatalysis